Hepatocellular Carcinoma With Portal Vein Tumor Thrombus Treated With Transarterial Chemoembolization and Sorafenib vs.125Iodine Implantation - Hu, Hong-Tao; Luo, Jun-Peng; Cao, Guang-Shao; Li, Zhen; Jiang, Ming; Guo, Chen-Yang; Yuan, Hang; Yao, Quan-Jun; Geng, Xiang; Park, Jung-Hoon; Cheng, Hong-Tao; Jiang, Li; et al. (Frontiers in Oncology, 2021)
Background and Aims This study investigated the feasibility, safety, and efficacy of transarterial chemoembolization (TACE) combined with CT-guided 125iodine seed implantation for treatment of hepatocellular carcinoma (HCC) with first-branch portal vein tumor thrombosis (PVTT). Methods This prospective, controlled, multicenter study included HCC patients with Barcelona Clinic Liver Cancer stage C disease and PVTT in the right and/or left portal veins. Patients were treated with either TACE and sorafenib or TACE and CT-guided 125iodine seed implantation and regularly evaluated for clinical response and adverse events, with treatment termination resulting from declining clinical status, loss to follow-up, or death. Results This study demonstrated a significant between-group difference in median overall survival (OS); therefore, it was terminated early. A total of 123 patients were included in this study, with 52 patients in the TACE-sorafenib group and 71 patients in the TACE-125iodine group, without significant differences in baseline characteristics between groups. The median OS was 8.3 months (95% CI: 6.105–10.495) in the TACE-sorafenib group and 13.8 months (95% CI: 9.519–18.081) in the TACE-125iodine group. In a subgroup analysis of type IIa versus type IIb PVTT, the median OS was 17.5 months for type IIa and 7.1 months for IIb in the TACE-125iodine group. The median OS was 9.3 months for IIa and 4.0 months for IIb in the TACE-sorafenib group. Univariate and multivariate analyses confirmed that the PVTT type and treatment strategy were significant independent factors affecting OS. The objective response rates (ORR) for intrahepatic lesions and PVTT showed significant differences between groups. Most patients in both groups experienced minor adverse events related to TACE. The overall incidence of sorafenib-related adverse events or toxic effects was 90.4% in TACE-sorafenib group. In the TACE-125iodine group, the incidence of pneumothorax and minor hepatic subcapsular hemorrhage were 7.04% and 9.86%, respectively. Conclusions This study showed that TACE-125iodine treatment significantly enhanced survival of patients with HCC and type II PVTT, especially subtype IIa, with minimal adverse events. Clinical Trial Registration Chinese Clinical Trials Database, identifier ChiCTR-ONN-16007929.